Re-Claiming Justice and Community: The Community Council Project of Toronto - Proulx, Craig (My University, 2001)
Aboriginal peoples, particularly urban Aboriginal peoples, are discriminated against and over-represented throughout the Canadian Criminal justice system. I review specific colonial and postcolonial actions that lead to Aboriginal over-representation and explore how the diversion program of the Community Council Project (CCP) provides justice for the Aboriginal peoples of Toronto. This research aims to investigate the under-researched intersection between alternative justice practive, individual and community healing, and identity in an urban Aboriginal community. The CCP appropriates a non-Aboriginal diversion format and combines it with culture-specific Aboriginal restorative justice traditions, and pan-Aboriginal discourse, to assist clients in the process of healing. This research illustrates how community based justice restores and/or transforms the identity of Aboriginal clients. I indicate how individuals are healed, and how they are reintegrated into the Aboriginal community of Toronto. Subsequently, I discuss how healthy individual and community identities can be fostered through CCP justice philosophy and practice. Finally, I delineate the role of the CCP in how Aboriginal "community" is conceived of and practiced in Toronto. In so doing I offer a new perspective on the concept of community creation in Toronto. This ethnography encompasses issues of crime causation, indigenous justice knowledge and practice; healing; tradition and culture change; personal and community ownership and empowerment; self-government and community constitution, and legal pluralism. Therefore, it contributes to, and expands the boundaries of current Aboriginal, anthropological and criminological knowledge about alternative justice.
Keywords: Philosophy; Philosophy